S116 Cell-dissociated haemophilus influenzae and bacteria-associated inflammatory mediators in the airways of patients with chronic obstructive pulmonary disease. (15th November 2017) - Thulborn, SJ; Ceroni, A; Haldar, K; Mistry, V; Cane, J; Brightling, CE; Barer, MR; Bafadhel, M
Abstract : Background: Patients with COPD have a susceptibility to respiratory tract infections associated with increased pulmonary inflammation. Bacteria can reside within the host as cell-associated (attached to host cells via adhesins, pili or biofilm formation) or cell-dissociated bacteria. It is unclear how bacteria-to-cell interactions affect pulmonary inflammation and whether these levels differ over an exacerbation time course. We sought to investigate the effects of Haemophilius influenzae cell-interaction upon airway inflammation and whether the levels of H. influenzae bacteria and cell-dissociated bacteria differ over an exacerbation time course. Methods: Cell differential counts were carried out on sputum samples as per standard protocol. Bacterial DNA was extracted and H.influenzae was quantified using qPCR from the sputum plug (contains cell-associated and dissociated bacteria) and the sputum cell-free supernatant (cell-dissociated bacteria only). Inflammatory mediators (IL-1α, TNF-α, IL-8 and neutrophil elastase (NE)) were measured in the sputum supernatant using commercial assays. Results: 63 patients (77% male; average age of 69 (45–88); FEV1 percentage predicted of 53%; mean percentage neutrophil count in sputum of 65%) at stable state were analysed. Levels of H. influenzae in the supernatant only correlated with the sputum total cell count (r=0.38; p=0.03). Levels of H. influenzae in the plug correlated with inflammatory mediators (sputum neutrophil percentage r=0.42, p=0.01; sputum macrophage percentage r=−0.35, p=0.04; IL-1α r=0.36, p=0.03; IL-8 r=0.49, p<0.01; NE r=0.40, p=0.02). The exacerbation time course in 10 paired COPD subjects was examined. There was no significant difference in H. influenzae levels in the plug (p=0.89) (figure 1 A). However, there was a significant increase in levels in the supernatant over the exacerbation time course (p=0.05) (figure 1 B). Conclusion: H. influenzae levels in the sputum plug appear to have much more of an effect on airway inflammation than levels of cell-dissociated H. influenzae suggesting that cell-associated bacteria may be a driver of airway inflammation in COPD. Further investigation into this highly complicated relationship needs to be conducted.